Numerical Simulation of Epidemic Prevention and Ventilation Efficiency in Indoor Spaces with Partitions and an Air curtain - Kun-Liang Hsieh; Yu-Hsuan Lee; Che-Yin Lee; Shu-Yu Peng; Shi-Min Lee (Journal of Applied Science and Engineering, 2024)
In this study, computational fluid dynamics (CFD) were used to simulate the effect of a partition and air curtain on the concentration of a pollution source in an indoor space with different ventilation configurations. First, in the partition simulation, the performances of six different ventilation configurations were compared. Based on the results obtained, air curtain simulations were then carried out. In this study, carbon dioxide was chosen as the tracer gas in all simulations, and the realizable k − ε turbulence model was selected. In the partition simulation, a front-and-back ventilation configuration with ventilation inlets/outlets near the side walls (in diagonal) showed the best performance. This configuration was adopted for the air curtain simulation so as to investigate the effect of different air inlet velocities and air curtain velocities. It was found that as the height of the partition increases, although it has a higher chance of blocking the Covid-19 virus, it lowers the ventilation efficiency, resulting in the increase of carbon dioxide concentration in the indoor space. When the partition was replaced with an air curtain, it was found that the higher the height of the air curtain, the lower the carbon dioxide concentration in the indoor space. Compared with the partition, the air curtain can reduce the carbon dioxide concentration by up to 74.6%, indicating that the introduction of the air curtain can have an improving effect on the ventilation in the indoor space.